2014
DOI: 10.1017/cha.2014.20
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ Experiences of Early Parenthood – Preliminary Findings

Abstract: Parents are instrumental in the healthy development of their children, and consequently future generations, and should therefore be supported in their parental role. Using a Grounded Theory framework, 24 parents of 0- to 10-year-olds were interviewed about their experiences and preparation for parenthood. Despite their overall satisfaction, many felt underprepared, unsure, alone and inadequate during their transition to parenthood. Most of them felt like they struggled unnecessarily during the first year of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
2
3
0
Order By: Relevance
“…However, parents were interested in more information across all areas, although the topics of interest to parents differed depending on whether parents had a baby or were expecting their first baby, reflecting the differing needs of parents across their baby's development. This finding is consistent with previous qualitative work showing that parents lack information about the transition to parenthood (Deave et al., ; R. Sanders, Lehmann, & Gardner, ) and with studies of parents with older children indicating that parents want additional information about a range of parenting topics (e.g., Devolin et al., ). Thus, despite the plethora of information available to parents, even well‐educated, well‐supported parents require additional support, pointing to the need for interventions that target all parents in a population and foster a nurturing environment for all children (Biglan et al., ).…”
Section: Discussionsupporting
confidence: 90%
“…However, parents were interested in more information across all areas, although the topics of interest to parents differed depending on whether parents had a baby or were expecting their first baby, reflecting the differing needs of parents across their baby's development. This finding is consistent with previous qualitative work showing that parents lack information about the transition to parenthood (Deave et al., ; R. Sanders, Lehmann, & Gardner, ) and with studies of parents with older children indicating that parents want additional information about a range of parenting topics (e.g., Devolin et al., ). Thus, despite the plethora of information available to parents, even well‐educated, well‐supported parents require additional support, pointing to the need for interventions that target all parents in a population and foster a nurturing environment for all children (Biglan et al., ).…”
Section: Discussionsupporting
confidence: 90%
“…Perhaps unsurprisingly, mothers expressed feelings of inadequacy, powerlessness, exhaustion and anxiety in the immediate months post-birth. These findings are consistent with existing research on early parenthood (Deave, Johnson & Ingram, 2008;Sanders, Lehmann & Gardner, 2014) and demonstrate how, in spite of the availability of information and care provided by healthcare professionals, parents are not always prepared or equipped for motherhood and often experience feelings of stress and insecurity. In both the above studies, participants' engagement with supports was varied, but indicated a need for more timely and relevant interventions to improve the experiences of motherhood.…”
Section: Discussionsupporting
confidence: 89%
“…The findings suggest that programmes such as the PIN, can provide important practical and emotional support to foster parental confidence and promote parent-child attachment. Parents are often ill-prepared for parenting (e.g., Sanders, Lehmann & Gardner, 2014) but the mothers in our study, reported high levels of satisfaction with the PIN programme and its delivery, as well as perceived benefits such as reduced parental stress and isolation and improved parental capacity. Improvements in parent-infant responsiveness and the parent-infant relationship were widely reported by parents and facilitators alike.…”
Section: Resultsmentioning
confidence: 62%
“…Moreover, the majority of the sample (80.0%) reported that they try to explain the reasons to their child, but they experience distress at the same time when they cannot meet their child's purchase requirements, and 20.0% of the participants answered that they feel remorse and guilt, which corresponds to percentages in each of the four income categories. Contemporary parents are bombarded with so many consumption choices and opportunities that they feel guilty and anxious about whether they make the right decisions for their children (Lobstein, 2013;Sanders et al, 2014). Additionally, they feel anxious about whether their consumption patterns meet the model of the "good" parent (Nair, 2013;Sidebotham, 2001).…”
Section: Discussionmentioning
confidence: 99%